Intergeneric and geomorphological variations in Symbiodiniaceae densities of reef-building corals in an isolated atoll, central South China Sea. (February 2021) - Liang, Yanting; Yu, Kefu; Pan, Ziliang; Qin, Zhenjun; Liao, Zhiheng; Chen, Biao; Huang, Xueyong; Xu, Lijia
Abstract: The healthy status of corals in the isolated atolls of the central South China Sea (SCS) remains unclear. Symbiodiniaceae density (SD) can effectively reflect the thermal tolerance and health of hard corals. Here, the SDs of 238 samples from the Huangyan Atoll (HA) were analyzed. The results revealed significantly intergeneric and geomorphological differences in SD. Intergeneric variation may reflect that corals with high SD have stronger thermal tolerance. Geomorphic analysis showed that the SDs at the outer reef slope were higher than in the lagoon. Hydrodynamics and sea surface temperature were likely the main influencing factors. Most notably, corals in SCS HA had higher SDs than those at neighboring reefs, indicating that their thermal tolerance were strong, which may be related to HA's local upwelling. These results suggest that the HA has the potential to serve as a refuge for corals, but increasing human disturbance limit its function. Graphical abstract: Unlabelled Image Highlights: Coral Symbiodiniaceae density (SD) shows intergeneric and spatial differences. Corals with high SD in South China Sea (SCS) have stronger thermal tolerance. Corals at outer reef slope of SCS atoll possess higher SDs than those at lagoon. Corals in SCS Huangyan Atoll have higher SDs than those at neighboring reefs. Human disturbances may limit the function of potential refuges for SCS corals.